Pengaruh Model RME Berbasis Etnomatematika Terhadap Kemampuan Literasi Matematika Siswa Kelas IV SD Gugus 17 Kota Bengkulu - Tivani Sandra Witha; Victoria Karjiyati; Pebrian Tarmizi (Universitas Bengkulu, 2020)
This study aims to determine the effect of ethnomatemics based Realistic Mathematics Education models on the mathematical literacy ability of grade IV elementary school students in the 17th city of Bengkulu on flat construction material. This research is a quantitative research. The research method used was quasi-experimental research using the matching only pretest-posttest control group design. The population in this study was the Elementary School Cluster 17 Bengkulu City. The sampling technique uses cluster random sampling. The sample in this study were students of class IV B Elementary School 04 Bengkulu City as an experimental class and students of class IV C Elementary School 11 Bengkulu as a control class. The research instrument used in the form of tests in the form of essay questions provided through pretest and posttest. The instrument used in the study was a test sheet in the form of a breakdown problem for the context of mathematical literacy. Based on the t-test calculation of students' posttest results, there is a tcount of 4.24> ttable of 2.01, so it can be concluded that there is an influence of using ethnomatemics-based Realistic Mathematic Education models on the ability of mathematical literacy in the context components of class IV students in Cluster 17 Bengkulu City